2020
DOI: 10.1038/s41598-020-62092-x
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of sex pheromones and binding specificity of pheromone binding protein 4 in Tryporyza intacta (Lepidoptera: Crambidae)

Abstract: The recognition of chemical signal including volatile odorants and pheromones is very important in the olfactory physiological behaviors of insects, such as avoiding predators, seeking food and mating partners. The sugarcane borer, Tryporyza intacta is the most harmful insect in sugarcane region in Southeast Asia and Southern China, however, the study of their molecular biology and physiology was limited. Here we demonstrated that the sex pheromone (E11-16:Ald: Z11-16:Ald = 7:3) were most effective to T. intac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Only two PflaPBPs were involved in this study, while 3~4 PBPs have been identified in some lepidopteran species [74,75]. These two PflaPBPs were originally identified from an antenna Illumina high-throughput transcriptome (unpublished data) in P. flammans, and their binding affinity for Z-9-hexadecenal and (Z, Z, Z)-9, 12, 15-octadecatrienal was also confirmed.…”
Section: Discussionmentioning
confidence: 72%
“…Only two PflaPBPs were involved in this study, while 3~4 PBPs have been identified in some lepidopteran species [74,75]. These two PflaPBPs were originally identified from an antenna Illumina high-throughput transcriptome (unpublished data) in P. flammans, and their binding affinity for Z-9-hexadecenal and (Z, Z, Z)-9, 12, 15-octadecatrienal was also confirmed.…”
Section: Discussionmentioning
confidence: 72%
“…The crude constituents of ES2 combine a variety of biological activities, including biocontrol, protein inhibitor, neurotoxin, antioxidant, immunostimulant, and anticancer activities. The compound 1-naphthylamine has antitumor 41 , antimicrobial 42 , and biocontrol activities against a lepidopteran pest, Tryporyza intacta 43 . S-adenosylmethioninaminium has anticancer activity 44 , whereas Brevianamid F and Palitantin have antimicrobial activity 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that hydrogen bonds and hydrophobic cavity may play important roles in the olfactory recognition process of OBP3 protein to host-plant volatiles. A great number of studies reported that different subfamilies of insect OBPs were involved in recognition and transport of semiochemical components and olfactory signals through the hemolymph in chemosensory organs [9][10][11][12][13][14] . For instance, Li et al found that Eastern honey bee, Apis cerana OBP2 had two key amino acids, Ser123 and Lys51 by docking analysis and site-directedmutagenesis, exhibiting important olfactory physiological function in visiting ower and pollination of Eastern honey bee 12 .…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Generally, OBPs can carry lipophilic volatiles of host and prey to the olfactory receptor (Ors) cells through hemolymph circulation of antennae and function in the rst step of insect odor reception 9 . PBPs are mainly involved in the chemical communication of sex pheromones between male and female pests and bene cial insects, which are produced in the pheromone glands (PG) located on the abdomen terminals 10 .…”
Section: Introductionmentioning
confidence: 99%